Optimizing Disaster Response and Mitigation through Digital Communication, Visualization, and Jabar Command Center: A Comprehensive Analysis - Darmawan, Ferry; Fardiah, Dedeh; Rinawati, Rini (KnE Social Sciences, 2024)
Effective disaster response and mitigation requires integrating advanced technologies in an increasingly connected world. This research investigates the synergistic role of digital communication, visualization, and the Jabar Command Center ( JCC) in optimizing disaster management strategies. Focusing on the West Java region, this research comprehensively analyzes how digital communication channels enhance information dissemination, and how visualization techniques aid situational awareness during disasters. By exploring the functions of the JCC, this research assesses the effectiveness of utilizing integrated digital communication for a timely and coordinated response. The case study research method was used to analyze qualitative and quantitative data collected through observation and focus group discussions, so that this research contributes to understanding the interaction between digital communication, visualization, and disaster response to provide optimal recommendations for optimizing these components in building a resilient disaster management system. The results show the role of integrated digital communication as a key factor in disaster mitigation in today’s digital era. Keywords: disaster management, digital communication, visualization techniques, comprehensive analysis